Ambient air pollution, lung function and COPD: cross-sectional analysis from the WHO Study of AGEing and adult health wave 1. Issue 1 (17th December 2020) - Elbarbary, Mona; Oganesyan, Artem; Honda, Trenton; Kelly, Patrick; Zhang, Ying; Guo, Yuming; Morgan, Geoffrey; Guo, Yanfei; Negin, Joel
Abstract : Background: Long-term exposure to ambient air pollution leads to respiratory morbidity and mortality; however, the evidence of the effect on lung function and chronic obstructive pulmonary disease (COPD) in older adult populations is inconsistent. Objective: To address this knowledge gap, we investigated the associations between particulate matter (PM), nitrogen dioxide (NO2 ) exposure and lung function, as well as COPD prevalence, in older Chinese adults. Methods: We used data from the WHO Study on global AGEing and adult health (SAGE) China Wave 1, which includes 111 693 participants from 64 townships in China. A cross-sectional analysis explored the association between satellite-based air pollution exposure estimates (PM with an aerodynamic diameter of ≤10 µm [PM10 ], ≤2.5 µm [PM2.5 ] and NO2 ) and forced expiratory volume in one second (FEV1 ), forced vital capacity (FVC), the FEV1 /FVC ratio and COPD (defined as post-bronchodilator FEV1 /FVC <70%). Data on lung function changes were further stratified by COPD status. Results: Higher exposure to each pollutant was associated with lower lung function. An IQR (26.1 µg/m 3 ) increase in PM2.5 was associated with lower FEV1 (−71.88 mL, 95% CI –92.13 to –51.64) and FEV1 /FVC (−2.81 mL, 95% CI −3.37 to –2.25). For NO2, an IQR increment of 26.8 µg/m 3 was associated with decreases in FEV1 (−60.12 mL, 95% CI –84.00 to –36.23) and FVC (−32.33 mL, 95% CI –56.35 to –8.32). A 31.2 µg/m 3 IQR increase in PM10 was linked to reduced FEV1 (−8.86 mL, 95% CI −5.40 to 23.11) and FEV1 /FVC (−1.85 mL, 95% CI −2.24 to –1.46). These associations were stronger for participants with COPD. Also, COPD prevalence was linked to higher levels of PM2.5 (POR 1.35, 95% CI 1.26 to 1.43), PM10 (POR 1.24, 95% CI 1.18 to 1.29) and NO2 (POR 1.04, 95% CI 0.98 to 1.11). Conclusion: Ambient air pollution was associated with lower lung function, especially in individuals with COPD, and increased COPD prevalence in older Chinese adults.